(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Ultraviolet (UV-X) corneal collagen cross-linking (CXL) involves photopolymerization of corneal collagen and in recent decades has been commonly employed for the treatment of stage 2 to 3 keratoconus. The high-intensity illumination of the UV-X™ 2000 Crosslinking System (Avedro, Inc., Waltham, Massachusetts) provides accelerated CXL (A-CXL), reducing treatment time threefold (to 10 minutes) compared with conventional CXL protocol. Purpose: To assess 24-month outcomes of A-CXL for stage 2 to 3 progressive keratoconus. Material and Methods: One hundred and nineteen patients (167 eyes) who underwent ACXL for keratoconus were included in this study. At 24 months, ocular changes were assessed in 40 eyes. A-CXL was carried out using the UV-X™ 2000 Crosslinking System at an irradiation intensity of 9 mW/cm?. Results: Mean astigmatism decreased by 1.15 D to 3.02 ± 1.73 (SD) D (for n=40 eyes) and mean corneal refractive power as assessed by Kmax decreased by 3.4 D to 54.4 ± 6.62 (SD) D (median value, 54.3 D; n=40 eyes) at 24 months compared to baseline values. Mean thinnest local corneal thickness increased by 3.0 ?m (mean value, 462.7± 34.3 (SD) ?m; median value, 455.5 ?m; n=40 eyes; р = 0.009), mean uncorrected visual acuity increased by 0.2, and mean best-corrected visual acuity increased by 0.25 at 24 months compared to baseline values. Of the 40 eyes examined at 24 months, BCVA improved in 34 eyes (85%). Conclusion: A-CXL for stage 2 to 3 progressive keratoconus resulted in a steady state of the pathological process, decrease in astigmatism by 1.15 D, decrease in corneal refractive power as assessed by Kmax by 3.4 D, and an increase in thinnest local corneal thickness by 3.0 ?m for the total study cohort, and improvement in BCVA in 85% of eyes at 24 months.